2016
DOI: 10.1155/2016/6984270
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 Inhibits Nucleus Pulposus Cells’ Degeneration through Targeting ERK 1/2

Abstract: We first investigated the difference in microRNA expression between normal NP cells and degenerative NP cells using gene chip. We have found that the expression of ERK1/2 was decreased with overexpression of miR-155 in normal nucleus pulposus cell. Expression of ERK1/2 was increased with inhibition of miR-155. Overexpression or inhibition of miR-155 had no effects on the expression level of mRNA ERK1/2 in nucleus pulposus cell, which showed that miR-155 affected the expression of pERK1/2 after transcription of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
(25 reference statements)
2
23
0
Order By: Relevance
“…Although their interaction mechanisms have not been analyzed in IDD, the roles of some miRNAs and lncRNAs have been confirmed in IDD and other diseases. For example, Wang et al (45) and Ye et al (46) demonstrated that miR-155 is downregulated in degenerative NP by microarray analysis; this was confirmed by reverse transcription-quantitative polymerase chain reaction. Zhang et al (47) demonstrated that upregulation of MALAT1 restrains IDD through suppressing inflammation and NP apoptosis, and promoting cell proliferation (47).…”
Section: Discussionmentioning
confidence: 87%
“…Although their interaction mechanisms have not been analyzed in IDD, the roles of some miRNAs and lncRNAs have been confirmed in IDD and other diseases. For example, Wang et al (45) and Ye et al (46) demonstrated that miR-155 is downregulated in degenerative NP by microarray analysis; this was confirmed by reverse transcription-quantitative polymerase chain reaction. Zhang et al (47) demonstrated that upregulation of MALAT1 restrains IDD through suppressing inflammation and NP apoptosis, and promoting cell proliferation (47).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, miR-155 can decrease the expressions of KRAS protein and mRNA [ 48 ]. Interestingly, miR-155 is the identified miRNA which regulates nucleus pulpous cells degeneration through directly targeting ERK1/2 [ 49 ]. Our data showed that miR-155-3p inhibited KRAS and pERK1/2 expression in EBs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, treatment of bovine NP cells with IGF-1 combined bone morphogenetic protein 7 (BMP-7) synergistically promoted aggrecan accumulation by enhancing Akt activity [ 52 ]. Accumulating evidence suggests that dysregulation of microRNAs (miRNAs) participates in disc degeneration [ 53 , 54 ]. Recently, Liu and colleagues observed that miR-4458 levels were significantly increased in degenerative human lumbar disc specimens [ 55 ].…”
Section: Roles Of the Pi3k/akt Pathway In The Pathogenesis Of Iddmentioning
confidence: 99%